El conflicto de Xinjiang: la minoría uigur y la política de Pekín - Pedro Domínguez, Nicolás De (UNISCI Discussion Papers, 2008)
The article analyses the current situation in Xinjiang and the growing unrest and alienation of the Uighur population. Therefore, the three axes of Chinese policy towards Xinjiang and its consequences are considered. In recent years, Beijing has combined systematic repression of any Uighur activity (resulting in massive violations of human rights), with the promotion of forced assimilation and the implementation of great development projects. Beijing has reasserted its position on Xinjiang, although resulting in a growing unease and alienation among most of Uighur population. Despite the calm of the past few years, the conflict is far enough from being resolved and a new cycle of turmoil and violence, as those that shook Xinjiang in the 1990s, is not fully dischargeable yet.